2021
DOI: 10.1016/j.jiac.2021.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Tocilizumab in COVID-19: The Cerrahpaşa-PREDICT score

Abstract: Background Cytokine release syndrome (CRS), characterized by overproduction of proinflammatory cytokines in the course of severe coronavirus disease 2019 (COVID-19), has been suggested as the major cause of mortality. Tocilizumab, a recombinant humanized monoclonal antibody against human IL-6 receptor, poses a therapeutic option for the treatment of CRS leading to severe acute respiratory syndrome in coronavirus-2 (SARS-CoV-2) infection. Methods We performed a single-ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
0
6
2
2
Order By: Relevance
“…So, the cut off of 60 years was selected for splitting the cases of survivors and deceased, and significant differences between groups (χ 2 = 6.907; DF = 1; p = 0.009) were found, and a risk of mortality 3.489 times higher in the group of patients over 60 years old compared to younger patients [OR = 3.489; 95% IC = (1.322, 9.209)] (Figure 3). The mortality rate in our case, treated with TCZ, was low (12.75%) compared to a recent Turkish study [9], which presented a 28 days-mortality rate in patients treated with TCZ (16.1%), for a similar median age (59 years old). Age over 65 years old was a significant risk factor for mortality, in our study.…”
Section: Resultscontrasting
confidence: 56%
See 1 more Smart Citation
“…So, the cut off of 60 years was selected for splitting the cases of survivors and deceased, and significant differences between groups (χ 2 = 6.907; DF = 1; p = 0.009) were found, and a risk of mortality 3.489 times higher in the group of patients over 60 years old compared to younger patients [OR = 3.489; 95% IC = (1.322, 9.209)] (Figure 3). The mortality rate in our case, treated with TCZ, was low (12.75%) compared to a recent Turkish study [9], which presented a 28 days-mortality rate in patients treated with TCZ (16.1%), for a similar median age (59 years old). Age over 65 years old was a significant risk factor for mortality, in our study.…”
Section: Resultscontrasting
confidence: 56%
“…Also, ACE-2 receptors are expressed in cardiovascular, gastro-intestinal and renal systems, representing an important target for SARS-CoV-2 virus. Severe pneumonia causes gas exchange obstruction, hypoxemia, anaerobic fermentation, intracellular acidosis [22] and all of these cause injury and apoptosis of cardiomyocytes [9]. A Chinese meta-analysis [14] showed the incidence of cardio-metabolic diseases in patients with severe forms of COVID-19, hospitalized in ICU (intensive-care units) for arterial hypertension, was twofold higher, cardio-cerebrovascular diseases threefold higher and for diabetes twofold higher, than non-ICU hospitalized cases.…”
Section: Resultsmentioning
confidence: 99%
“…In a study enrolling eighty-seven COVID-19 patients treated by Tocilizumab, Emre Eskazan A et al found that platelets count, procalcitonin, D-Dimer levels, RAO 2 S and the time from symptoms onset to Tocilizumab administration were associated with 28-day mortality of 16.1%. The Authors combined these variables in the CERRAHPASA-PREDICT score, whose positive and negative predictive values were 94.5% and 92.9%, respectively [29] . In another study enrolling two-hundreds and sixty-six COVID-19 patients treated with Tocilizumab, Mussini C et al identified sex, day-4, P/F after Tocilizumab administration, platelets count and CRP as independent risk factors for treatment failure and associated with 28-day mortality and mechanical ventilation [30] .…”
Section: Discussionmentioning
confidence: 99%
“…As COVID-19 is due to a hyperimmune response there has been interest in using immunosuppressant therapies in its management. Steroids have been found to be effective (Sterne et al, 2020) and there has been work on targeting specific cytokines such as IL-1 and IL-6 (Della-Torre et al, 2021;Eşkazan et al, 2021). The problem with using anti-cytokine therapy is that COVID-19 is associated with increases in multiple pro-inflammatory cytokines (Zaid et al, 2021) and it is not clear which one(s) to target.…”
Section: Platelets As a Drug Target In Infectionsmentioning
confidence: 99%